Conversion of Hard to Soft Magnetic Ferrite Nanowires by Paramagnetic Shielding - Xian-Lin Zeng; Indujan Sivanesarajah; Uwe Hartmann (Solids, 2023)
In this study, we investigate the magnetization behavior of coaxial nanowires fabricated through the sol-gel electrospinning method. Our analysis uncovers a significant reduction in coercivity for CoFe<semantics>2</semantics>O<semantics>4</semantics> nanowires when BaTiO<semantics>3</semantics> is used as the shell material, effectively transforming them from hard to soft magnetic. This intriguing behavior is attributed to the magnetization reversal effect at the interface between ferromagnetic and paramagnetic regions, and it is also observed in NiFe<semantics>2</semantics>O<semantics>4</semantics> and Fe<semantics>2</semantics>O<semantics>3</semantics> nanowires. Surprisingly, introducing a GdBa<semantics>2</semantics>Cu<semantics>3</semantics>O<semantics>7</semantics> shell induces a similar effect. Additionally, we employ magnetic impedance measurements on the coaxial nanowires, unveiling their potential for magnetic field sensing applications.